An analysis of genetic targets for guiding clinical management of follicular lymphoma. Issue 12 (1st December 2020) - Alonso-Alonso, Ruth; Rodriguez, Marta; Morillo, Daniel; Cordoba, Raul; Piris, Miguel A
ABSTRACT: Introduction : Follicular lymphoma (FL) is one of the most common non‐Hodgkin lymphoma (NHL) types, where genomic studies have accumulated potentially useful information about frequently mutated genes and deregulated pathways, which has allowed to a better understanding of the molecular pathogenesis of this tumor and the complex interrelationship between the tumoral cells and the stroma. Areas covered : The results of the molecular studies performed on Follicular Lymphoma have been here reviewed, summarizing the results of the clinical trials so far developed on this basis and discussing the reasons for the successes and failures. Searches were performed on June 1 st, 2020, in PubMed and ClinicalTrials.gov. Expert opinion : Targeted therapy for follicular lymphoma has multiple opportunities including the use of epigenetic drugs, PI3K inhibitors, modifiers of the immune stroma and others. Data currently known on FL pathogenesis suggest that combining these treatments with immunotherapy should be explored in clinical trials, mainly for patients with clinical progression or adverse prognostic markers. Association of targeted trials with dynamic molecular studies of the tumor and serum samples is advised. Chemotherapy-free approaches should also be explored as first-line therapy for FL patients.